2022
DOI: 10.1093/cid/ciac161
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in Hospitals: Effects of Aerosol-Generating Procedures, HEPA-Filtration Units, Patient Viral Load, and Physical Distance

Abstract: Background Transmission of covid-19 can occur through inhalation of fine droplets or aerosols containing infectious virus. The objective of this study was to identify situations, patient characteristics, environmental parameters and aerosol-generating procedures (AGPs) associated with airborne SARS-CoV-2 virus. Methods Air samples were collected near hospitalised covid-19 patients and analysed by RT-qPCR. Results were related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…51 Likewise, Thuresson et al found that the number of positive air samples with SARS-CoV-2 detection was similar in subjects treated with versus without respiratory support (HFNC or NIV). 52 Thus, we may conclude that neither NIV nor CPAP is an AGP. Vented masks should be avoided for patients with airborne disease; if tolerated, a helmet with an air cushion around the neck may be preferred.…”
Section: Noninvasive Ventilationmentioning
confidence: 87%
“…51 Likewise, Thuresson et al found that the number of positive air samples with SARS-CoV-2 detection was similar in subjects treated with versus without respiratory support (HFNC or NIV). 52 Thus, we may conclude that neither NIV nor CPAP is an AGP. Vented masks should be avoided for patients with airborne disease; if tolerated, a helmet with an air cushion around the neck may be preferred.…”
Section: Noninvasive Ventilationmentioning
confidence: 87%
“…▪ Two trials in the systematic review reported lower COVID-19 symptom scores with HEPA filtration (Daga et al 2021). ▪ Thuresson et al (2022) found that adding a mobile HEPA-filtration unit to rooms with regular ventilation was associated reduced SARS-CoV-2 RNA in the air. ▪ HEPA/UV filtration units greatly reduced particulate matter counts of all sizes (Sloof et al (2022).…”
Section: Evidence Of Effectivenessmentioning
confidence: 98%
“…▪ Two studies, (Conway Morris et al 2022, Daga et al 2021 were assessed as having high risk of bias concerns. ▪ Two observational studies (Sloof et al 2022, Thuresson et al 2022) and the modelling study (Buchan et al 2020) were assessed as having low risk of bias.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Efforts to prevent transmission should focus on all key measures, with recommendations that take into consideration the level of community spread and the risk of transmission from mildly symptomatic or asymptomatic individuals. SARS CoV-2 is primarily transmitted through small and large respiratory droplets 101 , 102 , 103 . Long range transmission by small particle aerosols can happen and forms the basis of the current CDC guidance for transmission-based precautions.…”
Section: Infection Prevention Considerationsmentioning
confidence: 99%